Relationships among Ocular Blood Flow Shown by Laser Speckle Flowgraphy, Retinal Arteriosclerotic Change, and Chorioretinal Circulation Time Obtained by Fluorescein Angiography - Hironori Osamura; Tomoaki Shiba; Takashi Itokawa; Tadashi Matsumoto; Yuichi Hori (Journal of Ophthalmology)
Purpose. To determine the correlations among the mean blur rate (MBR) in the optic nerve head (ONH) shown by laser speckle flowgraphy (LSFG), retinal arteriosclerosis, and the circulation time obtained by fluorescein angiography (FA). Method. We evaluated 118 patients and assessed their time of choroidal flush, arm-to-retina time, and early and late phases of retinal circulation time (RT: sec) obtained by FA. The severity of retinal arteriosclerosis was classified according to the Scheie classification. The MBR values throughout the ONH (MBR-A), in the tissue (MBR-T), and in the vessels (MBR-V) were analyzed. Results. Patients with retinal vein occlusion (RVO) showed prolonged early and late phases of RT compared to other ocular diseases. Single and multiple regression analyses showed that the MBR-V and Scheie classification were significantly associated with both the choroidal flush and arm-to-retina times. The incidences of RVO and MVR-V were significantly associated with the early phase of RT, and the incidences of RVO, MBR-V, Scheie classification, and gender were revealed to be factors independently contributing to the late phase of RT. Conclusion. MBR-V in the ONH and retinal arteriosclerosis are important contributing factors for the circulation time of each stage obtained by FA.